2016
DOI: 10.5539/jas.v8n10p241
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seed Storage Techniques on Germinability and Storability of Cowpea (Vigna unguiculata (L) Walp)

Abstract: <p>This study was set to investigate the germinability and storability of the newly released cowpea genotypes and secondly the influence of different storage materials under ambient storage condition on seed vigour and germination over time. The experiment was laid in a Split-split plot design with four replicates. The main plot was duration (0, 30, 60 and 90 days), while Storage material (polyethylene bag, cotton bag and glass container) was sub plot and the four cowpea genotypes were sub-sub plot. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Studies carried out by Bortey et al (2016) showed that loss of the quality attributes of the seed can occur faster in one genotype than another even when exposed to the same storage conditions, since the genotypes exude solutes at differential rates due to their ability to resist aging. As the imbibition time elapses, more solutes are released to the outside due to the level of deterioration of the cell membranes (Batista et al, 2012).…”
Section: Electrical Conductivity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out by Bortey et al (2016) showed that loss of the quality attributes of the seed can occur faster in one genotype than another even when exposed to the same storage conditions, since the genotypes exude solutes at differential rates due to their ability to resist aging. As the imbibition time elapses, more solutes are released to the outside due to the level of deterioration of the cell membranes (Batista et al, 2012).…”
Section: Electrical Conductivity Testmentioning
confidence: 99%
“…Low EC values are associated with good seed quality (Arun et al, 2017). On the other hand, the conventional germination method is the most reliable, despite demanding more time and has been applied in cowpea to be compared with other methods (Bortey et al, 2016;Moura et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As seed quality deteriorates during storage, vigour declines before loss in standard germination [30]. Moreover, reported that farmers in the developing world still store their produce including seed under the ambient environment [15]. Some researchers concluded that, storage under ambient conditions has been observed to affect seed quality in general and germination in particular [11].…”
Section: Effect Of Seed Storage Period and Storage Environment On Seed Qualitymentioning
confidence: 99%
“…For 1000-seed weight determination, 100 seeds were randomly selected and weighted. The weight obtained was then multiplied by ten (Bortey, Sadia & Asibuo, 2016). Hectoliter weight (Kg/hL) was estimated in triplicate using a 1-liter graduated cylinder filled with seeds consistently and uniformly before weighting.…”
Section: Seed Physical Characteristicsmentioning
confidence: 99%